Andamiaje digital un puente entre la ZDP y la IA - Delgado Pumalpa, Jeisson Santiago (Revista Universitaria de Informática RUNIN, 2024)
The article explores how the integration of Artificial Intelligence (AI) in education transforms the teaching-learning process by acting as a digital scaffolding within the Zone of Proximal Development (ZPD). AI personalizes learning, adjusting tasks and offering feedback in real time, facilitating the development of skills such as computational thinking. However, its implementation faces challenges, such as the lack of technological resources and the need for teacher training. Despite these obstacles, AI has the potential to significantly improve the quality of education, promoting inclusive and effective learning in primary schools.